SIMULATION OF DRILL STRING VIBRATION DUE TO RISER'S OSCILLATION - AL BATATI, NABIL (2015)
In deep sea drilling, there are two major components of drilling tools that are subjected to vibration, namely the marine riser and the drilling pipe. Analysis of vibration in the marine riser and drill pipes are two topical areas that have individually received considerable attention by researchers in the past. For the marine riser, the focus was on the vortex-induced vibration (VTV) in different shear and flow regime. On the other hand, the focus on the drill pipes was on different vibratory modes and resonance. While these two subjects are interrelated, borne by the fact that the marine riser encapsulates and protects the drill pipe, they have been little attempt to investigate them together as an assembly.